In Situ CT Tensile Testing of an Additively Manufactured and Heat-Treated Metastable ß-Titanium Alloy (Ti-5Al-5Mo-5V-3Cr) - Julius Hendl (MDPI AG, 2021)
Additive manufacturing has been considered a suitable process for developing high-performance parts of medical or aerospace industries. The electron beam powder bed fusion process, EB-PBF, is a powder bed fusion process carried out in a vacuum, in which the parts are melted using a highly focused electron beam. The material class of metastable β-titanium alloys, and especially Ti-5Al-5Mo-5V-3Cr, show great potential for use as small and highly complex load-bearing parts. Specimens were additively manufactured with optimised process parameters and different heat treatments used in order to create tailored mechanical properties. These heat-treated specimens were analysed with regard to their microstructure (SEM) and their mechanical strength (tensile testing). Furthermore, in situ tensile tests, using a Deben CT5000 and a YXLON ff35 industrial µ-CT, were performed and failure-critical defects were detected, analysed and monitored. Experimental results indicate that, if EB-PBF-manufactured Ti-5553 is heat-treated differently, a variety of mechanical properties are possible. Regarding their fracture mechanisms, failure-critical defects can be detected at different stages of the tensile test and defect growth behaviour can be analysed.